(untitled) (Indian Journal of Child Health, 2022)
Joubert syndrome (JS) is a rare autosomal recessive disorder that has variable phenotype but characteristic magnetic resonance imaging (MRI) findings. “Molar tooth” appearance of cerebellar peduncles and “bat-wing” appearance of the fourth ventricle are the classically described MRI findings. Herein, we describe JS in three siblings, products of a second-degree consanguineous marriage, who presented with developmental delay, abnormal eye movements, and impaired vision. The axial MRI in all three siblings revealed the classic MRI findings described in the JS.